2010
DOI: 10.2298/jsc100322115e
|View full text |Cite
|
Sign up to set email alerts
|

Sage-called plant species sold in Turkey and their antioxidant activities

Abstract: Sage is commonly consumed as a herbal tea in Anatolia, where not only Salvia species, but also Sideritis species are called "sage" by the local people. Therefore, it was decided to investigate the most common species of sage-called plants sold in aktars. Eighty-seven samples randomly purchased from 21 provinces throughout Turkey were identified, which finally led to the identification of 7 species; Salvia tomentosa, Salvia fruticosa, Sideritis congesta, Sideritis pisidica var. termessi, Sideritis arguta,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 12 publications
3
9
0
Order By: Relevance
“…The results of total phenolics content of the sample analysed was 131.34±8.39 gallic acid equivalents mg (GAE) g -1 of extract. Total phenolic content of S. tomentosa extracted with various solvents ranged widely, among 10 and 275 μg GAE mg -1 Erdogan-Orhan, et al, 2010). In our studies result, was 131.34 mg (GAE) g -1 , which is support to with our results.…”
Section: In Vitro Antifungal Resultssupporting
confidence: 90%
“…The results of total phenolics content of the sample analysed was 131.34±8.39 gallic acid equivalents mg (GAE) g -1 of extract. Total phenolic content of S. tomentosa extracted with various solvents ranged widely, among 10 and 275 μg GAE mg -1 Erdogan-Orhan, et al, 2010). In our studies result, was 131.34 mg (GAE) g -1 , which is support to with our results.…”
Section: In Vitro Antifungal Resultssupporting
confidence: 90%
“…Additionally, results may be affected by geographical location of the plants, ecological conditions, and climate (Papageorgiou et al 2008;Kallithraka et al 2009). Erdogan-Orhan et al (2010) reported that total flavonoid content of S. tomentosa was 46.31 mg quercetin equivalent g -1 , which is consistent with our results. The flavonoid content of S. tomentosa decreased in the second harvesting year, whereas it did not change significantly through cultivation and storage.…”
Section: Total Phenolic and Flavonoid Contents And Antioxidant Activitysupporting
confidence: 93%
“…Total phenolic content of S. tomentosa extracted with different solvents ranged broadly, between 10 and 275 µg GAE mg -1 (Tepe et al 2005;Erdogan-Orhan et al 2010). However, in our case, it was between 49.27 and 63.26 mg GAE g -1 dw.…”
Section: Total Phenolic and Flavonoid Contents And Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Up to date, the essential oil [19][20][21][22] and fatty acid [23] compositions of S. pisidica have been studied. Also, antioxidant, antiacetylcholinesterase activity and phenolic composition of the aqueous and ethanolic extract of S. pisidica have been reported by Erdogan-Orhan et al [24] and Özkan [12].…”
Section: Introductionmentioning
confidence: 99%